Analisis Pengaruh Belanja Daerah dan PDRB terhadap Peningkatan Pendapatan Asli Daerah (PAD) di Kalimantan Barat - Dina Rizky Ramadhani; Widya Nur Fadila; Nita Safira (Direktorat Sistem Perbendaharaan, 2024)
The increase in local own-source revenue, as one of the sources of the district's funding, is influenced by local economic activities, which are reflected in the value of gross regional domestic product (GRDP). Local government expenditure, as stated in the regional government budget, also becomes one of many factors contributing to the increase in local own-source revenue. That is because the consumption of local government expenditure will enhance the local economic activities. This study examines the effect of GRDP and local government spending on the increase in local own-source revenue in Kalimantan Barat. The data used in this study consisted of 140 data taken from 14 districts/cities within Kalimantan Barat in 10 years (2013-2022) and analyzed using the random effect model (REM) panel data regression model. The results showed that GRDP and local government expenditure significantly affect local own-source revenue in Kalimantan Barat. On the other hand, GRDP and local government expenditures significantly increase local own-source revenue in Kalimantan Barat on a partial basis. Based on the study, researchers recommend that to increase local own-source revenue through the economy (GRDP), the government needs to carry out economic transformation by focusing on optimizing industrial estates. The government must also increase allocations on productive local government expenditures such as capital expenditure and immediately issue regional regulations regarding regional taxes.